The Exemplary Method and Its Urgency in Moral Education According to the Perspective of Abdullah Nashih Ulwan - Hidayat, Mohamad Samsul; Fitri, Rizqi Annisa; Mardiyanto, Agus; Mustofa, Edi; Jaenullah, Jaenullah; Yusuf, Yusuf (CV. BImbingan Belajar Assyfa, 2024)
This study examines the role and importance of the exemplary method in moral education through the lens of Abdullah Nashih Ulwan's teachings. Utilizing a content analysis approach, the research investigates the concepts presented in Ulwan's seminal work, Tarbiyatul Aulad Fil Islam, and related literature. The study highlights that Ulwan advocates for educators to serve as role models, demonstrating virtues such as humility, courage, patience, honesty, piety, and firmness. These attributes are essential in shaping children's character and moral compass. The research underscores the urgency of integrating moral education into educational curricula, emphasizing that educators should embody these virtues not only in their professional roles but also in personal conduct. The findings suggest that adopting Ulwan's exemplary method can significantly enhance the effectiveness of moral education and contribute to the development of a well-rounded, ethical society.